Identification and In Vitro Antimicrobial Susceptibility of Brucella Species Isolated from Human Brucellosis - Rohaidah Hashim; Norazah Ahmad; Jama’ayah Mohamed Zahidi; B. Y. Tay; Azura Mohd Noor; Sakina Zainal; Hazwani Hamzah; S. H. Hamzah; T. S. Chow; P. S. Wong; K. N. Leong (International Journal of Microbiology)
Brucellosis is a world-wide zoonotic disease with a major impact on the public health. Due to the high risk of laboratory acquired infection, limited laboratory investigations were performed on this organism, including detailed identification and susceptibility study. Brucella melitensis is the commonest aetiological agent for human brucellosis in this region. The in vitro susceptibility pattern against selected antimicrobial agents was assessed using E-test. All isolates were noted to be sensitive to all the antimicrobial agents tested except for rifampicin where elevated MIC > 1 μg/mL was noted in 30 out of 41 isolates tested.